Solution of Fuzzy Non-Homogeneous DifferentialEquation under Trapezoidal Fuzzy Number - Bawane, Dnyaneshwar P.; Ladke, Lemraj S. (Communications in Mathematics and Applications, 2025)
This article proposes a result for first order fuzzy non-homogeneous differential equation under trapezoidal fuzzy number as preliminary value. We have used a method of interval arithmetic on α-cut interval of trapezoidal fuzzy number to obtained a general solution. We have presented a result of non-homogeneous fuzzy differential equation for four distinct circumstance of real valued functions tangled in differential equations. Also, an example of non-homogeneous first order linear fuzzy differential equation under trapezoidal fuzzy number as initial condition is being solved to verify the result at the end.